Gerakan Sekolah Peduli Kanker: Edukasi Hidup Sehat Untuk Pencegahan Kanker Di UPT SDN 060831 Medan - Martha Sutriska Sagala; Enny Selawaty Boang Manalu; Brenda Marissa Peranginangin; Jenika Nainggolan; Elsaria Tinambunan (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Cancer is one of the leading causes of death in Indonesia, and its prevention can begin at school age through the adoption of healthy lifestyle behaviors. Low health literacy among students, teachers, and parents poses a challenge in cancer prevention efforts. This community service program aimed to improve knowledge, awareness, and healthy lifestyle behaviors in the school community through the School Cancer Awareness Movement at UPT SDN 060831 Medan. The method used was Participatory Action Research (PAR), which actively involved students, teachers, and parents. The program stages included preparation, joint planning, interactive education, training for teachers and Cancer Ambassadors, practical actions such as Fruit Day and morning exercise, and evaluation. The results showed an average increase in student knowledge by 38% and teacher knowledge by 42%, the development of healthy habits such as bringing healthy lunches, reducing unhealthy snacks, and participating in physical activities. Additionally, new school practices emerged, such as regular Fruit Day, morning exercise, and the establishment of a Cancer Information Corner. This program proved effective in fostering behavioral change and building a culture of healthy living in the school environment.